Western Union Telegram from Blair Clark to Jane Tolmach - Blair Clark:::::: (1968)
A Western Union telegram that informs Jane Tolmach that Senator Eugene McCarthy will appear on national CBS television with three congressmen to discuss the Republican nomination, issues facing America, and the Democratic Party. The message lists broadcast times across multiple time zones and advises checking local schedules for variations. It is signed by Blair Clark, McCarthy's campaign manager, who encourages her to tune in.